Embracing Generational Diversity: Reducing and Managing Workplace Conflict - André, Shelley (Operating Room Nurses Association of Canada Journal, 2018)
The phrase “Nurses Eat Their Young” is an expression that is all too familiar within the nursing profession. Intergenerational differences can exacerbate pre-existing tendencies to put new nurses through their paces or orientate them using ‘trial by fire methods’ that were experienced by older nurses experienced when beginning their careers.1 With four generations present in the workplace, and widely different approaches to work ethics, it is important to gain an understanding of these differences and to learn how to work efficiently and effectively together. Embracing and valuing each generation for its strengths and recognizing generational diversities in the workplace will help create a dynamic, rich, engaging, and fulfilling work environment in which all nurses feel valued and supported by their team. Nurse managers and leaders have a pivotal role in creating professional workplaces that attract and retain staff. They do so by defining the culture of the nursing unit, and the organization as a whole, through modeling behaviour that communicates, to the entire team, what is considered acceptable behaviour and displays zero tolerance for bullying. Effective mentoring can also cultivate understanding of generational differences in nursing while facilitating productive learning and fostering effective working relationships.